Power electronic converter topologies for switched reluctance motor towards torque ripple analysis. (2022) - Deepak, M.; Janaki, G.; Bharatiraja, C.
Highlights: This paper discuss the classification of converters structure analysis the two level converter and multi-level converter with their benefits, fault tolerant, control complex and applications. The converters are compared with their performance characteristics, low cost and high reliability. Asymmetrical bridge or classical converter fast demagnetization effect play a vital role in SRM converter controller. The classical converter with three different topology 6/4, 8/6, 10/8 is connected to switched reluctance motor using matlalab Simulink analysis the torque ripple can attain 82.19%, 62.37%, 59.14%. Abstract: The power converter circuit plays a vital role in electric drives. The converters performance has a significant impact on the drive performance as well as cost. There are different motors applied in electric drives, this study primarily focused on torque ripple analysis of Switched Reluctance Motor (SRM) drive and its converter topologies. The SRM salient poles have the stator outer side and the rotor inner side, which is different from the other polyphase machines. Although there have been a number of converters for SRM drives through the years, each converter has its own set of benefits and drawbacks. The choice of a converter is dictated by the application, this article includes a comparative analysis of SRM converter topologies, two level converters branches and multi-level converters branches were discussed in detail with schematic diagram. Based on the survey it is found that an asymmetrical bridge converter best suits for Electric vehicle application due to its advantage of reducing fault tolerant, fast demagnetization and regenerative braking capability. This paper presents the study of 10 kW SRM Drive controlled by asymmetrical bridge converter, in three different phase modification mode such as 6/4, 8/6 and 10/8 using MATLAB simulation and the torque ripples are analysed for each case.